2018
DOI: 10.3390/ijerph15051031
|View full text |Cite
|
Sign up to set email alerts
|

Removing Organic Matter and Nutrients from Pig Farm Wastewater with a Constructed Wetland System

Abstract: Pollutants from pig farms in Mexico have caused problems in many surface water reservoirs. Growing concern has driven the search for low-cost wastewater treatment solutions. The objective of this research was to evaluate the potential of an in-series constructed wetland to remove nutrients from wastewater from a pig farm. The wetland system had a horizontal flow that consisted of three cells, the first a surface water wetland, the second a sedimentation cell, and the third a subsurface flow wetland. The vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 44 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…High salt concentrations in the water or soil can reduce the portability of water and adversely affect plant productivity [ 52 ]. Furthermore, high EC can cause the inability of vegetation to compete for ions in water and soil causing toxicity of particular ions [ 53 ] such as chloride, sodium, etc. However, in terms of irrigation classes for fitness use [ 51 ], EC fell between good and marginal values.…”
Section: Discussionmentioning
confidence: 99%
“…High salt concentrations in the water or soil can reduce the portability of water and adversely affect plant productivity [ 52 ]. Furthermore, high EC can cause the inability of vegetation to compete for ions in water and soil causing toxicity of particular ions [ 53 ] such as chloride, sodium, etc. However, in terms of irrigation classes for fitness use [ 51 ], EC fell between good and marginal values.…”
Section: Discussionmentioning
confidence: 99%
“…ICW Some of these technologies are relatively new and have been used to treat highly loaded waters where a high oxygen demand is necessary, e.g., run-off from anti-icing fluids in airports [192], waters from food production [193], and petroleum industry discharges [194]. ICW also included in this review shows the use of hybrid systems in different configurations and operational schemes in the region; e.g., recirculation of HSSFW and VF systems [39,88], hybrid systems (combining HSSFW and VF systems) [41,140,161] aerated systems [67, 103,121], using algae turf filters [89] and microalgae ponds [98], evapotranspirative systems [114], and the use electroactive bacteria-based constructed wetlands (METland) [58] in the region. The ICW has been used to treat wastewater from domestic sewage [89,114,121], coffee production [67,103], swine [161], and landfill leachate [88].…”
Section: Fwsmentioning
confidence: 99%
“…For instance, the higher HRT or lower pollutant loading rate brings pollutants to have a higher rate of contact time within the treatment system (Reed et al 1995); favors greater chances of TSS sedimentation, and COD degradation, including high nutrient absorption and retention (Guo et al 2017), and improves the effluent quality. According to Mora-orozco et al (2018), a comparison of different treatment wetland efficiencies with the removal of solids and organic matter at different HRTs revealed that the 10 days HRT showed the highest removal efficiency than 5 days HRT. Sultana et al (2016) also showed that 8 days HRT removed 100% COD.…”
Section: Pollutant Removal Efficiencymentioning
confidence: 99%
“…Many studies have also recognized that sufficient contact time has a significant role in the TSS and COD removal since it offers both particles to settle, and improve the removal efficiencies through adhering rather than absorbed by vegetation (Mora-orozco et al 2018;Winanti et al 2018). Also, the biological process has a main role in the removal of organic matter through microbiological degradation with bacteria attached to macrophyte roots (Winanti et al 2018).…”
Section: Pollutant Removal Efficiencymentioning
confidence: 99%
See 1 more Smart Citation